King of the world : Muhammad Ali and the rise of an American hero - Remnick, David (1998)
"There were mythic sports figures before him - Jack Johnson, Babe Ruth, Joe Louis, Joe DiMaggio - but when Cassius Clay burst onto the sports scene from his native Louisville in the 1950s, he broke the mold. He changed the world of sports and went on to change the world itself. As Muhammad Ali, he would become the most recognized face on the planet. This unforgettable story of his rise and self-creation, told by a Pulitzer Prize-winning writer, places Ali in a heritage of great American originals." "Cassius Clay grew up in the Jim Crow South and came of athletic age when boxers were at the mercy of the mob. From the start, Clay rebelled against everything and everyone who would keep him and his people down. He refused the old stereotypes and refused the glad hand of the mob. And, to the confusion and fury of white sportswriters, who were far more comfortable with the self-effacing Joe Louis, Clay came forward as a rebel, insistent on his political views, on his new religion, and, eventually, on a new name. His rebellion nearly cost him the chance to fight for the heavyweight championship of the world." "King of the World features some of the pivotal figures of the 1960s - Malcolm X, Elijah Muhammad, John F. Kennedy - and its pivotal events: the civil rights movement, political assassinations, the war in Vietnam."--Jacket
ch. 1. Underground man -- ch. 2. Two minutes, six seconds -- ch. 3. Mr. Fury and Mr. Gray -- ch. 4. Stripped -- ch. 5. Bicycle thief -- ch. 6. Twentieth-century exuberance -- ch. 7. Secrets -- ch. 8. Hype -- ch. 9. Cross and the crescent -- ch. 10. Bear hunting -- ch. 11. "Eat your words!" -- ch. 12. Changeling -- ch. 13. "Save me, Joe Louis" -- ch. 14. Gunfire -- ch. 15. Anchor punch -- ch. 16. What's in a name?
Includes bibliographical references and index
Keywords: Ali, Muhammad, -- 1942-2016; Boxers (Sports) -- United States -- Biography; Biography